Changing communities and increases in the prevalence of depresion: is there a relationship? - Krause, Mariane; Pontificia Universidad Católica de Chile (2016)
The article analyses the impact of individualization processes on community-level determinants of health in postmodern societies, taking depression as an example. The analysis shows how the evolution of the broader social context towards forms of organization focused on the individual and on competition in a market economy implies the vanishing of traditional communities and therefore of their health-supportive functions, thus endangering their ability to fulfill the needs of belonging, mutual support, and identity. The analysis also relates this evolution to cultural phenomena and to recent studies about culture-gene coevolution, implying that the effects of community decline are expected to be even greater in collectivist societies. Through its multidimensional conceptual analysis, this paper aims to contribute to further uncovering the interactions of psychological, psychosocial, and biological factors in mental health